(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Subroto AP, Aditama R, Tanjung ZA, Utomo C, Liwang T. 2021. Identification of conserved peptide upstream open reading frames (CPuORFs) in oil palm (Elaeis guineensis) genome. Biodiversitas 22: 1829-1838. Upstream open reading frame (uORF) translation serves as one of several modulating mechanisms in gene expression. Conserved peptide uORF is a rare subset of uORF containing a peptide sequence that is conserved among eudicot families and negatively regulates the translation of its adjacent main ORF (mORF). This research aimed to identify oil palm CPuORFs by conducting a homology search between Arabidopsis (Arabidopsis thaliana) and rice (Oryza sativa) CPuORF databases against the existing oil palm (Elaeis guineensis) genome. Using alignment by Hidden Markov Model (HMM) approach, 48 oil palm CPuORFs were discovered which were later divided into 24 homology groups (HG) based on its gene ontology. The high degree of sequence homology indicates a high conservation CPuORFs among oil palm, Arabidopsis and rice. The CPuORFs peptide sequence conservation between oil palm progenies was later validated by sequencing of CPuORF22 and CPuORF29 as a reference, from several DxP Tenera crosses, individual Duras from different origins and American oil palm (Elaeis oleifera). This is the first study of oil palm CPuORF discovery which might provide a better understanding of gene expression regulation in oil palm.